Ultrasonic Frequency Analysis of Adhesively Bonded Joints - Jansen, H.P.; Elburg, B. van; Veen, E.S. van; Platenkamp, D.J. (MDPI, 2025)
Bonded joints are commonly used for aircraft construction. The non-destructive testing of these components for debonds can be performed using traditional NDI. However, in the case of weak bonds and “kissing bonds”, inspection becomes more difficult. In this work, we have investigated weak bonds that have been produced by contaminating the bondline interface with different release agents. By carrying out an analysis of ultrasonic data from the frequency domain, the bondline thickness can be determined. Additionally, indications of the presence of contaminants/weak bonds can be detected at specific frequencies, while the effects of a non-uniform bondline thickness can be suppressed by averaging the power around the selected frequency. Mechanical testing at different locations showed that indications in the frequency domain were able to find one weak bond, while the other indications showed no decrease in lap shear strength